2020
DOI: 10.1186/s12875-020-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Stratified primary care versus non-stratified care for musculoskeletal pain: qualitative findings from the STarT MSK feasibility and pilot cluster randomized controlled trial

Abstract: Background: Stratified care involves subgrouping patients based on key characteristics, e.g. prognostic risk, and matching these subgroups to appropriate early treatment options. The STarT MSK feasibility and pilot cluster randomised controlled trial (RCT) examined the feasibility of a future main trial and of delivering prognostic stratified primary care for patients with musculoskeletal pain. The pilot RCT was conducted in 8 UK general practices (4 stratified care; 4 usual care) with 524 patients. GPs in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…However, the length of time taken to recruit participants was over twice as long as expected (28 rather than 12 weeks), and GPs completed the Keele STarT MSK Tool in fewer patient cases than we had hoped for (they used it in 32% of patient cases when the target was > 50%). The nested qualitative study findings [41] and feedback discussions with participating GPs explored the reasons why only two of the four prespecified pilot trial success criteria were met. These identified in the particular challenge of using the EMR template and stratified care intervention when MSK pain was not the primary reason for the consultation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the length of time taken to recruit participants was over twice as long as expected (28 rather than 12 weeks), and GPs completed the Keele STarT MSK Tool in fewer patient cases than we had hoped for (they used it in 32% of patient cases when the target was > 50%). The nested qualitative study findings [41] and feedback discussions with participating GPs explored the reasons why only two of the four prespecified pilot trial success criteria were met. These identified in the particular challenge of using the EMR template and stratified care intervention when MSK pain was not the primary reason for the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The study design was a pragmatic, feasibility and pilot, two-parallel arm (1:1 ratio), cluster RCT in 8 general practices, with a nested qualitative study reported separately [41]. A cluster RCT was chosen over an individual patient randomisation design as stratified MSK care involves GPs using a slightly different consultation approach following specific training, as well as the use of a bespoke electronic medical record (EMR) template, which was only possible to implement at a practice level without causing a high probability of intervention contamination across arms [42].…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In previous studies physiotherapists, physicians as well as patients described positive experiences or expectations for such a use of the STarT-Back-Tool. 3,27,28 The participants' perceptions about which professional should carry out the risk stratification varied. It was stated that physicians, like physiotherapists, could do it, while some questioned if the job could be done by clinic assistants.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we agreed on evidence-based recommended matched treatment options for patients in each subgroup following a systematic review [ 22 ] and expert consensus process [ 23 ]. Third, we conducted an external feasibility and pilot randomized trial with 524 patients from 8 general practices (4 intervention and 4 control) [ 21 , 24 ]. The pilot trial confirmed the acceptability of using a stratified care approach in primary care consultations and also helped to refine our recruitment, retention, and sample size estimates, ahead of the main trial.…”
Section: Introductionmentioning
confidence: 99%